Corporate intranet failures: interpreting a case study through the lens of formative context. (23rd June 2006) - Stenmark, Dick
Although intranets are well-established information environments, companies complain that their intranets are left under-utilised. Consulting the standard management literature, it seems the medicine typically prescribed is tighter management control. In this study, we examine the use of and the attitudes towards an international company's intranet. Although the respondents' testimonies seem to be in line with existing literature, advocating centrality and control, we argue that this is only a superficial pattern. When the informants' statements are not accepted as facts but instead critically questioned to reveal the underlying attitudes, an alternative view emerges. Applying the notion of formative context to the intranet, we uncover the institutionalised cognitive frames governing the actors' reasoning and explain the clashes between the espoused theory of intranet usage and the theory-in-use. In compliance with previous studies of information infrastructure, we conclude that intranet management, too, is centred on control as the supreme management objective.